Cardiac and mitochondrial function in HIV-uninfected fetuses exposed to antiretroviral treatment. - Laura García-Otero; Marta López; Mariona Guitart-Mampel; Constanza Morén; Anna Goncé; Carol Esteve; Laura Salazar; Olga Gómez; Josep María Martínez; Berta Torres; Sergi César; Glòria Garrabou; et al. (PLoS ONE, 2019)
BACKGROUND:Mitochondrial toxicity related to maternal combined antiretroviral treatment (cART) may have an impact on the heart of HIV-exposed uninfected (HEU) fetuses. Our objective was to evaluate fetal cardiovascular and mitochondrial biomarkers in HIV pregnancies. METHODS:Prospective cohort including 47 HIV-infected and 47 non HIV-infected pregnancies. Fetal echocardiography was performed at 26-32 weeks of pregnancy. Umbilical cord blood and placental tissue were collected to study mitochondrial DNA content (mtDNA) (ratio 12SrRNA/RNAseP) and mitochondrial function (cytochrome c oxidase, COX, enzymatic activity) normalized by mitochondrial content (citrate synthase, CS). RESULTS:HEU fetuses showed hypertrophic hearts (left myocardial wall thickness: HIV mean 3.21 mm (SD 0.81) vs. non-HIV 2.72 (0.42), p = 0.012), with signs of systolic and diastolic dysfunction (isovolumic relaxation time: HIV 52.2 ms (8.85) vs. non-HIV 42.5 ms (7.30); p<0.001). Cord blood mitochondrial content was significantly increased in HIV-exposed fetuses (CS activity: HIV 82.9 nmol/min.mg of protein (SD 40.5) vs. non-HIV 56.7 nmol/min.mg of protein (28.4); p = 0.007), with no differences in mtDNA content and COX activity. Both myocardial and mitochondrial mass parameters were significantly associated with zidovudine exposure. CONCLUSIONS:HEU fetuses showed signs of increased myocardial and mitochondrial mass associated with maternal zidovudine treatment, suggesting a fetal adaptive response to cART toxicity.